Methods of sports genetics: dermatoglyphic analysis of human palmarprints (information 2) - Serhiyenko L.P; Lyshevskaya V.M (Kharkov National Pedagogical University, 2010)
Information is generalized about the dermatoglyphic analysis of hands of hands of man. The quantitative dermatoglyphic indexes of hands of hands are presented for youths and girls of the Podol region of Ukraine. The quantitative indexes of palm's dermatoglyphics are rotined for youths and girls of Ukrainian and Russian nationality in Kharkov. The most informing dermatoglyphic indexes of hands of hands which it is possible to use in sporting genetics are certain. Formed recommendation on technology of dermatoglyphic analysis of hands of hands of man in sporting genetics.